Risk Communication and Crisis Communication in Infectious Disease Outbreaks in Germany: What Is Being Done, and What Needs to be Done. (7th May 2014) - Dickmann, Petra; Biedenkopf, Nadine; Keeping, Sam; Eickmann, Markus; Becker, Stephan
Abstract Objective Risk communication plays a central role in the management of infectious disease. The World Health Organization's 2005 International Health Regulations have highlighted the need for countries to strengthen their capacities in this area to ensure effective responses to public health emergencies. We surveyed laboratories, hospitals, and public health institutions in Germany to detail the current situation regarding risk communication and crisis management and to identify which areas require further development. Methods A mixed methods approach was adopted. An initial questionnaire was distributed to relevant persons in laboratories and hospitals, and semistructured interviews were conducted with selected participants. Representatives from state public health authorities, federal agencies, and media also were interviewed to add additional contextual information to the questionnaire responses. Results Based on the responses received, the universal sense among key stakeholders was that risk communication and crisis communication measures must be improved. Collaborative working was a consistent theme, with participants suggesting that a partnering strategy could help to improve performance. This approach could be achieved through better coordination between groups, for example, through a knowledge-sharing policy. Conclusions More research is needed on how such collaboration might be implemented, along with a general conceptual framework for risk communication to underpin the overall strategy. (Disaster Med Public Health Preparedness. 2014;0:1-6)